Ingestion of sodium plus water improves cardiovascular function and performance during dehydrating cycling in the heat - Hamouti, N.; Fernández-Elias, V. E.; Ortega, J. F.; Mora-Rodriguez, R. (Scandinavian Journal of Medicine & Science in Sports, 2014)
We studied if salt and water ingestion alleviates the physiological strain caused by dehydrating exercise in the heat. Ten trained male cyclists (inline image : 60 ± 7 mL/kg/min) completed three randomized trials in a hot-dry environment (33 °C, 30% rh, 2.5 m/s airflow). Ninety minutes before the exercise, participants ingested 10 mL of water/kg body mass either alone (CON trial) or with salt to result in concentrations of 82 or 164 mM Na+ (ModNa+ or HighNa+ trial, respectively). Then, participants cycled at 63% of inline image for 120 min immediately followed by a time-trial. After 120 min of exercise, the reduction in plasma volume was lessened with ModNa+ and HighNa+ trials (-11.9 ± 2.1 and -9.8 ± 4.2%) in comparison with CON (-16.4 ± 3.2%; P < 0.05). However, heat accumulation or dissipation (forearm skin blood flow and sweat rate) were not improved by salt ingestion. In contrast, both salt trials maintained cardiac output (?1.3 ± 1.4 L/min; P < 0.05) and stroke volume (appr. 10 ± 11 mL/beat; P < 0.05) above CON after 120 min of exercise. Furthermore, the salt trials equally improved time-trial performance by 7.4% above CON (?289 ± 42 vs 269 ± 50 W, respectively; P < 0.05). Our data suggest that pre-exercise ingestion of salt plus water maintains higher plasma volume during dehydrating exercise in the heat without thermoregulatory effects. However, it maintains cardiovascular function and improves cycling performance.